Motion Vector Sharing and Bitrate Allocation for 3D Video-Plus-Depth Coding. (4th June 2008) - Daribo, Ismaël; Tillier, Christophe; Pesquet-Popescu, Béatrice
Abstract : The video-plus-depth data representation uses a regular texture video enriched with the so-called depth map, providing the depth distance for each pixel. The compression efficiency is usually higher for smooth, gray level data representing the depth map than for classical video texture. However, improvements of the coding efficiency are still possible, taking into account the fact that the video and the depth map sequences are strongly correlated. Classically, the correlation between the texture motion vectors and the depth map motion vectors is not exploited in the coding process. The aim of this paper is to reduce the amount of information for describing the motion of the texture video and of the depth map sequences by sharing one common motion vector field. Furthermore, in the literature, the bitrate control scheme generally fixes for the depth map sequence a percentage of 20% of the texture stream bitrate. However, this fixed percentage can affect the depth coding efficiency, and it should also depend on the content of each sequence. We propose a new bitrate allocation strategy between the texture and its associated per-pixel depth information. We provide comparative analysis to measure the quality of the resulting3 D + t sequences.